Fluorescence-labeled neopeltolide derivatives for subcellular localization imaging. Issue 28 (1st July 2019) - Yanagi, Shota; Sugai, Tomoya; Noguchi, Takuma; Kawakami, Masato; Sasaki, Makoto; Niwa, Shinsuke; Sugimoto, Asako; Fuwa, Haruhiko
Abstract : Fluorescent-labeled neopeltolide derivatives were rationally designed for cell imaging to elucidate their localization in the mitochondria and the endoplasmic reticulum. Abstract : Design, synthesis and functional analysis of fluorescent derivatives of neopeltolide, an antiproliferative marine macrolide, are reported herein. Live cell imaging using the fluorescent derivatives showed rapid cellular uptake and localization within the endoplasmic reticulum as well as the mitochondria.